Isolation of a unique hepatic stellate cell population expressing integrin α8 from embryonic mouse livers. Issue 6 (23rd April 2018) - Ogawa, Tomohiro; Li, Yuchang; Lua, Ingrid; Hartner, Andrea; Asahina, Kinji
Abstract : Background: Hepatic stellate cells (HSCs) play an important role in liver fibrogenesis. However, little is known about their phenotype and role in liver development. The aim of this study is to identify specific markers for embryonic HSCs.Results: Using antibodies against ALCAM and PDPN, we separated mesothelial cells (MCs) and HSCs from developing livers and identified integrin α8 (ITGA8) as a marker for embryonic desmin+ HSCs that are preferentially localized near the developing liver surface and α‐smooth muscle actin+ perivascular mesenchymal cells around the vein. A cell lineage–tracing study revealed that upon differentiation, MC‐derived HSCs or perivascular mesenchymal cells express ITGA8 during liver development. Using anti‐ITGA8 antibodies, we succeeded in isolating MC‐derived HSCs and perivascular mesenchymal cells from embryonic livers. In direct co‐culture, ITGA8+ mesenchymal cells promoted the expression of hepatocyte and cholangiocyte markers in hepatoblasts. In the normal adult liver, expression of ITGA8 was restricted to portal fibroblasts in the portal triad. Upon liver injury, myofibroblasts increased the expression of ITGA8.Conclusions: ITGA8 is a specific cell surface marker of MC‐derived HSCs and perivascular mesenchymal cells in the developing liver. Our data suggest that ITGA8+ mesenchymal cells maintain the phenotype of hepatoblast in liver development. Developmental Dynamics 247:867–881, 2018 . © 2018 Wiley Periodicals, Inc. Key Findings: Dynamic spatiotemporal Yap expression and subcellular localization suggest diverse functions in ocular tissues. Yap activity exerts not only its canonical function mediating progenitor proliferation and survival, but also non‐ canonical functions related to cell polarity and fate determination. Perturbations of Hippo-Yap signaling result in diverse ocular disorders.